2001
DOI: 10.1007/s005200000197
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, crossover comparison of standard-dose versus low-dose lenograstim in the prophylaxis of post-chemotherapy neutropenia

Abstract: The aim of this trial was to compare the severity of neutropenia, the frequency of hospital admission for fever or infection, and the use of antibiotics among patients treated with a standard dose of lenograstim (263 microg/day of Euprotin) and others treated with half of this dose (131.5 microg/day) and the cost-effectiveness of each of the two doses. In this single-center study, 44 patients with solid tumors, who were all receiving standard-dose chemotherapy regimens following previous neutropenia or were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Although there have been several reports on doses of G‐CSFs for prophylaxis of postchemotherapy neutropenia, there is little information for patients with nonsolid tumors and no information for patients with NHL who were treated with rituximab (Toner et al. , 1998; Juan et al. , 2001; Hara et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there have been several reports on doses of G‐CSFs for prophylaxis of postchemotherapy neutropenia, there is little information for patients with nonsolid tumors and no information for patients with NHL who were treated with rituximab (Toner et al. , 1998; Juan et al. , 2001; Hara et al.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on doses of G‐CSFs for prophylaxis of postchemotherapy neutropenia (Toner et al. , 1998; Juan et al. , 2001; Hara et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose lenograstim has also proven to be more cost-effective than standard-dose lenograstim. 13,14 One study also demonstrated a trend toward less bone pain, a common adverse effect of CSFs, with low-dose lenograstim. 14 This study aims to retrospectively analyze the effectiveness of low-dose filgrastim, 150 μg/day, in patients receiving adjuvant treatment for node-positive or node-negative breast cancer with docetaxel (75 mg/ m 2 ), doxorubicin (50 mg/m 2 ), and cyclophosphamide (500 mg/m 2 ) given simultaneously every 21 days for a total of six cycles.…”
mentioning
confidence: 95%
“…The decision to use low-dose filgrastim was based on the published effectiveness of low-dose lenograstim compared to standard-dose lenograstim in preventing febrile neutropenia and hospitalizations. 13,14 For convenience and prevention of wasting excess medication, a 150-μg/day filgrastim dose was chosen; two 150-μg filgrastim syringes can be prepared from a 300-μg filgrastim vial.…”
mentioning
confidence: 99%